A Randomized Controlled Clinical Study Comparing the Diagnostic Accuracy of the Histologic Prediction for Colorectal Polyps Depending on the Use of Either Magnified or Nonmagnified Narrow Band Imaging - Jin Joo Kim; Kyoung Sup Hong; Joo Sung Kim; Hyun Chae Jung (Korean Society of Gastrointestinal Endoscopy, 2015)
Background/Aims: The aim of this study was to compare the diagnostic capabilities of narrow band imaging (NBI) colonoscopy with and without optical magnification in differentiating neoplastic from nonneoplastic colorectal polyps. Methods: Between April 2012 and March 2013, 122 patients with colorectal polyps detected by using diagnostic conventional colonoscopy were prospectively enrolled. A total of 236 polyps were evaluated with NBI, in vivo in real time during therapeutic colonoscopy, by one experienced endoscopist. Whether magnification was used or not was determined by randomization. After an in vivo real-time endoscopic prediction of histology, all lesions were endoscopically excised. Surgical pathologic reports were used as the criterion standards. The sensitivity (Sn), specificity (Sp), positive predictive value (PPV), and negative predictive value (NPV) of identifying neoplastic polyps were calculated. Results: A total of 236 lesions with an average size of 5.6 mm in 122 patients were assessed (159 neoplastic, 77 nonneoplastic). The Sn, Sp, PPV, and NPV in differentiating neoplastic from nonneoplastic lesions with the magnified NBI were 97.5%, 83.3%, 94.0%, and 92.6%, respectively, whereas those of the nonmagnified NBI group were 97.5%, 85.1%, 91.7%, and 95.2%, respectively. Conclusions: Nonmagnified NBI colonoscopy distinguishes neoplastic from nonneoplastic colorectal polyps as accurately as does magnified NBI colonoscopy.